Trident: A dual oxygenation and fluorescence imaging platform for real-time and quantitative surgical guidance - Ségaud, Silvère; Baratelli, Luca; Felli, Eric; Bannone, Elisa; Cinelli, Lorenzo; Rodríguez-Luna, María Rita; Okamoto, Nariaki; Keller, Deborah S; de Mathelin, Michel; Lecler, Sylvain; Diana, Michele; Gioux, Sylvain (Frontiers in Photonics, 2022)
Despite recent technological progress in surgical guidance, current intraoperative assessment of tissue that should be removed (e.g. cancer) or avoided (e.g. nerves) is still performed subjectively. Optical imaging is a non-contact, non-invasive modality that has the potential to provide feedback regarding the condition of living tissues by imaging either an exogenously administered contrast agent or endogenous constituents such as hemoglobin, water, and lipids. As such, optical imaging is an attractive modality to provide physiologically and structurally relevant information for decision-making in real-time during surgery. The Trident imaging platform has been designed for real-time surgical guidance using state-of-the-art optical imaging. This platform is capable of dual exogenous and endogenous imaging owing to a unique filter and source combination, allowing to take advantage of both imaging modalities. This platform makes use of a real-time and quantitative imaging method working in the spatial frequency domain, called Single Snapshot imaging of Optical Properties (SSOP). The Trident imaging platform is designed to comply with all relevant standards for clinical use. In this manuscript, we first introduce the rationale for developing the Trident imaging platform. We then describe fluorescence and endogenous imaging modalities where we present the details of the design, assess the performance of the platform on the bench. Finally, we perform the validation of the platform during an in vivo preclinical experiment. Altogether, this work lays the foundation for translating state-of-the-art optical imaging technology to the clinic.